Detection of Burkholderia in the seeds of Psychotria punctata (Rubiaceae) – Microscopic evidence for vertical transmission in the leaf nodule symbiosis - Sinnesael, A.; Eeckhout, S.; Janssens, S.B.; Smets, E.; Panis, Bartholomeus; Leroux, O.; Verstraete, B. (Public Library of Science, 2018)
The bacterial leaf nodule symbiosis is a close interaction between endophytes and their plant hosts, mainly within the coffee family. The interaction between Rubiaceae species and Burkholderia bacteria is unique due to its obligate nature, high specificity, and predominantly vertical transmission of the endophytes to the next generation of host plants. This vertical transmission is intriguing since it is the basis for the uniqueness of the symbiosis. However, unequivocal evidence of the location of the endophytes in the seeds is lacking. The aim of this paper is therefore to demonstrate the presence of the host specific endophyte in the seeds of Psychotria punctata and confirm its precise location. In addition, the suggested location of the endophyte in other parts of the host plant is investigated.